Hubungan Dukungan Suami dengan Penggunaan Alat Kontrasepsi dalam Rahim (AKDR) di Puskesmas Labuhan Deli Kecamatan Labuhan Deli Kabupaten Deli Serdang Tahun 2023 - Sonia Novita Sari; Sri Hartini; Marlina Simbolon (STIKes Ibnu Sina Ajibarang, 2024)
The IUD is one of the most effective and safest long-term contraceptive methods, however use of this contraceptive method is still very low. The aim of the research was to determine the relationship between husband's support and the use of intrauterine contraceptives (IUD) at the Labuhan Deli Community Health Center, Labuhan Deli District, Deli Serdang Regency in 2023. The research method was a quantitative analytical survey with a cross sectional approach. The population of IUD family planning acceptors in May and June at the Labuhan Deli Community Health Center was 42 respondents. Chi square data analysis technique. The conclusion of this research is the relationship between husband's support and the use of intrauterine contraceptives (IUD) at the Labuhan Deli Community Health Center, Labuhan Deli District, Deli Serdang Regency with a p-value of 0.002. It is hoped that there will be more questions from health providers or more use of existing facilities as input for receiving information about health, especially the use of the IUD.